Are Audit Committees Overloaded? Evidence from the Effect of Financial Risk Management Oversight on Financial Reporting Quality - Ashraf, Musaib; Choudhary, Preeti; Jaggi, Jacob (Management Science, 2024)
Audit committee (AC) responsibilities have increased over time, prompting concerns that overloading the AC with too many duties may impair the AC’s ability to oversee financial reporting. Using new AC charter-based proxies to measure AC responsibilities, we find that an emphasis on the AC overseeing financial risk management (which is a noncore AC duty) is associated with worse financial reporting quality, as proxied by restatements—consistent with the argument of AC overload by distraction. This overload effect is attenuated when an AC has more directors to share duties or when the AC retains an expert auditor who can serve as a substitute for AC oversight. This overload effect is accentuated when AC members are busy with multiple board appointments or when the external auditor is busy with other audits. We also find that AC financial risk oversight is associated with more AC meetings and greater turnover of AC directors, consistent with the notion of overload. In sharp contrast, we find that greater AC oversight over internal controls (which is a core AC duty) is associated with improved financial reporting quality. Overall, we document that the nature of AC duties impacts the AC’s ability to promote financial reporting quality and that noncore duties may overload ACs. This paper was accepted by Suraj Srinivasan, accounting. Funding: The authors are grateful for funding provided by the Eller College of Management at the University of Arizona, the Broad College of Business at Michigan State University, and the Carson College of Business at Washington State University. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.00360 .